Pengembangan Model Pendidikan Anti Korupsi Terintegrasi dalam Pembelajaran Al-Islam dan Kemuhammadiyahan di Universitas Muhammadiyah Purworejo - Iyus Herdiana Saputra; Nasrudin Nasrudin (Cakrawala: Jurnal Studi Islam, 2015)
In the introductory stage, the preliminary research begins through literature study, and then doing in-depth interviews by involving lecturers, as well as doing field surveys by distributing questionnaire as the research instrument by using Likert scale in the form of check list. The instrument is used to measure the respondent’s attitude toward the needs of anti – corruption education in the right model. The result of the questionnaire shows the average scores = 4,1. It means that college students agree with anti – corruption education in UMP to be integrated into the learning of Al-Islam and Kemuhammadiyahan. The developmental stages involve 1) the product design (1st draft) by arranging the curriculum and the learning strategies, 2) Validating the design by consulting to the expert of curriculum and evaluating, as well as analyzing the 1st draft which is done by the lecturer of Al-Islam.Commonly, the expert considered that the curriculum is good enough and it only needs perfecting in the assessment section, 3) next, the revision of the product, 4) Evaluation and perfection, then 5) hypothetical model – the last model. In this last stage, it has resulted curriculum, syllabus, SAP and the model of learning strategies which are divided into two – in-class discussion model for the 1st – 6th semesters and model of general stadium through the activity of baitul arqam which is for the 7th and 8th semesters by inviting the law practitioners, ulama, KPK and community leaders. Then it is followed by the activity of Focus Group Discussion. After finishing the process of hypothetical model, the researchers socialize the product to the AIK lecturer as the user